Enhancing Air Traffic Management and Reducing Noise Impact: A Novel Approach Integrating Băneasa Airport with Otopeni RO Airport - Adina Cristina Toma; Grigore Cican; Daniel-Eugeniu Crunteanu (Applied Sciences, 2023)
Over the years, Bucharest’s Henri Coandă International Airport has registered a constant and high increase in air traffic, in terms of both passengers and aircraft movements. This paper presents a traffic diversion solution for the Otopeni RO airport, which aims to alleviate air traffic congestion by redirecting a proportion of the planes to the nearby airport at Băneasa. The primary challenge faced by diversion to Băneasa Airport is the proximity of residential areas to the runway at distances of less than 300 m, resulting in significant noise pollution issues. At Otopeni Airport, the main operators use aircraft equipped with CFM 56 turbo engines; therefore, this study begins with an evaluation of the noise directivity of a CFM aircraft engine via measurement. The data thus collected enabled the identification of the dominant frequencies in the acoustic spectrum of the engine noise. A resonant screen solution has been proposed as a solution for Băneasa Airport, emphasizing the importance of implementing solutions to address the noise pollution faced by those living near Băneasa Airport, due to its proximity to the residential area. Various configurations of perforated metal sheets with different perforation patterns were compared to the test performance of solid sheets to optimize noise absorption. Using the impedance tube tests to achieve the highest absorption coefficient, it was determined that the optimal distance between the perforated metal sheets and the resonant screen was 30 mm. Based on the CFM 56 turbo engine noise directivity and the impedance tube tests, a multitude of numerical simulations were conducted using the IMMI software (IMMI 2011). The simulations were performed for two scenarios with and without an acoustic barrier, accounting for the typical configuration of two engines on an aircraft. The results indicate a reduction of 15 dBA with the implementation of a 4-m-high acoustic barrier, in the case of a CFM 56 engine operating at full throttle while the aircraft is on the ground. Through numerical simulations, the optimized resonant screen demonstrated its potential to significantly reduce noise levels, thereby enhancing the overall acoustic environment and quality of life for the communities surrounding Băneasa Airport. The identified findings could serve as a basis for further research and the implementation of innovative solutions to manage air traffic and reduce the impact of aircraft noise in surrounding areas.